Circulating MicroRNAs as Potential Biomarkers in the Diagnosis of Neurosyphilis: A Case Control Study - Kai-Qi Wu; Su-Fang Zhang; Chao-Hui Bao; Xin Zou; Xin Gu; Cui-Ni Wang; Wei-Ming Gong; Mei Shi; Yong-Liang Lou; Jian Huang; Ping-Yu Zhou (Wolters Kluwer Health, 2021)
Abstract. Objective:. Laboratory diagnosis of neurosyphilis (NS) remains a great challenge. This study was the aimed to identify miRNA candidates as biomarkers to distinguish between NS, non-neurosyphilis, and healthy controls (HCs). Methods:. We analyzed miRNA expression profiles in peripheral blood mononuclear cells (PBMCs) from six patients with NS, eight patients with secondary syphilis (SS), and five HCs using microarray technology. The differentially expressed miRNAs were validated in 33 NS samples, 31 SS samples, and 30 HC samples using TaqMan miRNA real-time qPCR (qRT-PCR). Results:. Thirty-nine miRNAs were differentially expressed in SS and NS patients compared with HCs. Thirteen miRNAs were randomly selected to validate their expression levels in the same samples used in microarray assay by qRT-PCR. All miRNAs were upregulated in SS and NS samples compared with HC. qRT-PCR analysis of the expression of the 13 miRNAs in a second cohort (76 samples) showed that the average expression levels of nine miRNAs were higher in SS than in NS (SS: 0.185, NS: 0.136, P=3.8E-10), while the expressions of the other four miRNAs were lower in SS than in NS (SS: 0.000757, NS: 0.000873, P=0.022). ROC curve analysis of the 13 miRNAs showed the area under the curve value to be 1.00 for distinguishing SS patients from HCs, 1.00 for distinguishing NS patients from HCs, 1.00 for distinguishing SS and NS patients from HCs, and 0.968 for distinguishing NS from SS patients. Conclusion:. The present study is the first one that identified differentially expressed miRNAs in PBMCs from patients with NS. Our results suggest that the 13 candidate miRNAs in PBMCs may be novel noninvasive biomarkers for NS diagnosis.